A study of deviation in Terengganu from Syariah perspective / Ahmad Farhan Abdul Halim, Nur Syaqiera Md Nasir and Nurul Nadia Shariffudin - Abdul Halim, Ahmad Farhan; Md Nasir, Nur Syaqiera; Shariffudin, Nurul Nadia (2009)
Enforcement of law is a paramount aspect in ensuring the efficiency of laws. In general, this research attempts to discuss about the enforcement of law in the issue of deviation by emphasising on the Syariah Criminal Offences (Takzir) (Terengganu) Enactment of 2001. Besides, the research focuses on the methodologies on how those laws are enforced by Department of Islamic Religious Affairs of Terengganu by discussing vital aspects in identifying powers of enforcement of Syariah legal enforcement. Methods of gathering data used in this study are amongst others, through library research by focusing on statutes, practice orders and court cases. Interviews are also adopted. This study found that there are several lacunas in those laws, which must be solved despite numerous organizational weaknesses, management of human resource at the agency of enforcement and prosecution.